Pembangunan Berkelanjutan Pulau-Pulau Kecil di Wilayah Negara Perbatasan Melalui Penguatan Peran sebagai Pusat Pertumbuhan - Samsul Marif; Sudharto P. Hadi; Maryono Maryono (Prosiding Sains dan Teknologi, 2022)
The problem of small islands in the national border area related to development policy interventions is still lacking. Geographical position, raises problems in relation to regional accessibility. This is partly due to the remote geographical location, the economic scale of the business, inadequate transportation conditions, limited facilities and infrastructure such as electricity, roads, telecommunications, clean water and others. Small islands as an entity that has a size, special characteristics and vulnerabilities so that the planning and management of small islands requires a different format from large islands. In connection with these problems, it is necessary to increase development interventions through the role of strengthening the role as a center for sustainable growth. Through a descriptive approach with scalogram analysis and clustering, determining the role as a growth center with a coverage area of influence can be done. economic and socio-cultural. The center of growth and grouping of islands is an approach taken to provide direction for spatial planning for small islands. Keywords: Small Islands, Sustainable Development, Growth Center